Ileal perforation caused by cytomegalovirus in an immunocompetent patient - Guzman, Gloria M.; Olvera, Cinthia; Sevilla, Jose G.; Lopez, Carlos; Huerta, Karen (International Journal of Research in Medical Sciences, 2022)
Cytomegalovirus (CMV) is a subclinical infection that causes catastrophic consequences for patients, specifically those who are immunocompromised. In this article we review a 71-year-old male patient with history of ischemic cardiopathy, he begins with abdominal pain localized in right inferior quadrant. The abdominopelvic CT scan reported an acute complicated appendicitis with pneumoperitoneum. We realized a laparotomy, identifying an ileal perforation. CMV diagnosis was made by histological findings.